Emergence of Multiple Novel Inter-Genotype Recombinant Strains of Human Astroviruses Detected in Pediatric Patients With Acute Gastroenteritis in Thailand - Wei, Hongyu; Khamrin, Pattara; Kumthip, Kattareeya; Yodmeeklin, Arpaporn; Maneekarn, Niwat (Frontiers in Microbiology, 2021)
Objective: Human astrovirus (HAstV) is recognized as an important cause of acute gastroenteritis in children. Recombination between different genotypes of HAstV can contribute to diversity and evolution of the virus. This study aimed to investigate the emergence of HAstV recombinant strains in pediatric patients hospitalized with acute gastroenteritis in Chiang Mai, Thailand spanning 2011 to 2020. Methods: A total of 92 archival HAstV strains collected from pediatric patients with acute gastroenteritis during 2011 to 2020 were further characterized to identify the recombinant strains. The ORF1b and ORF2 junction region of each strain was amplified and sequenced. The obtained sequences were analysed in comparison with the reference sequences retrieved from GenBank database. Their genotypes were assigned using MEGA X software based on the partial ORF1b (RdRp) and ORF2 (capsid) regions, and the recombination breakpoints of recombinant strains were determined by SimPlot and RDP4 analyses. Results: Five inter-genotype recombinant strains with three recombination patterns of ORF1b/ORF2 of classic HAstV, HAstV8/HAstV1, HAstV8/HAstV3, and HAstV3/HAstV2, were detected. The recombination breakpoints of all strains were located at 3′-end region of ORF1b closed to the ORF1b/ORF2 junction. Conclusion: Several novel inter-genotype recombinant strains of classic HAstV genotypes were detected in pediatric patients with acute gastroenteritis in Chiang Mai, Thailand during the period of ten years from 2011 to 2020.